Disentangling Associations of Neighborhood Street Scale Elements With Physical Activity in Mexican School Children. (January 2016) - Lee, Rebecca E.; Soltero, Erica G.; Jáuregui, Alejandra; Mama, Scherezade K.; Barquera, Simón; Jauregui, Edtna; Lopez y Taylor, Juan; Ortiz-Hernández, Luis; Lévesque, Lucie
Promoting outdoor play and participation in sports and organized physical activities in children may depend on neighborhood characteristics. This study investigated associations between neighborhood streets and physical activities among Mexican children ( N = 1, 509, 6-11 years). Child sociodemographic characteristics and physical activity were measured in schools in Guadalajara ( n = 10), Mexico City ( n = 13), and Puerto Vallarta ( n = 3), Mexico, in 2012. Street segments within an 800 m radius around each school were measured using the Pedestrian Environment Data Scan. Most (75.8%) played outdoors; 47.4% participated in sports and 40% in organized physical activities. Fewer path obstructions and more pedestrian amenities were associated positively with outdoor play. Greater street cleanliness, more pedestrian amenities, and more path obstructions were associated with less participation in sports or organized activities. Walkability was negatively associated with all physical activities. Fostering safe and appealing streets may help promote outdoor play time, but not sports participation, for Mexican children.